Peran komunikasi sebagai daya tarik pelanggan koperasi mahasiswa - Fadhilah, Lailatul Iftitachatil (Maliki Interdisciplinary Journal, 2024)
The role of communication and the influence of cooperative service quality as an attractive force for Coopermart customers is the aim of writing the article. Proper cooperative management includes providing optimal service to customers and implementing cooperative management based on cooperative management functions. The success of cooperatives in achieving their goals is very dependent on the knowledge, appreciation and awareness of cooperatives possessed by their members and management. Kopma PB offers various types of tiered education and training which aims to increase the knowledge of members and management. In the role of communication between apprentices and customers, they also have their own SOP for service at Coopmart. Communication is very important to implement because this is one of the references in the success of a business. However, there are obstacles in communication, but every obstacle must have a solution to resolve the obstacle. Therefore, the role of communication is very important to attract customers at the UIN Malang co-opmart.